The crystal structure of 3-chloropropylammonium chloride, C3H9Cl2N - Muller Kina (Zeitschrift für Kristallographie - New Crystal Structures, 2021)
C3H9Cl2N, monoclinic, I2/a (no. 15), a = 8.7694(5) Å, b = 9.6963(6) Å, c = 14.8577(9) Å, β = 98.266(3)°, V = 1250.24(13) Å3, Z = 8, Rgt(F) = 0.0193, wRref(F2) = 0.0511, T = 200 K.